Pengaruh Cara Penangkapan, Fasilitas Penangan dan Cara Penanganan Ikan Terhadap Kualitas Ikan yang Dihasilkan - Metusalach Metusalach; Kasmiati Kasmiati; Ilham Jaya (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
The research was aimed at determining the effect of fishing techniques, handling facilities and method son the quality of the catch. The research employed four types of fishing gears, i.e. purse seine, cantrang,gillnet and boat-liftnet with five replicates each. Five species of the dominant catch were taken for qualitydetermination on-board, at landing sites, and after auctioning. The condition of handling facilities andmethods were evaluated. Fish transit time (time lapse between the fish lifting and auction process) was also determined. Results indicated that the fish quality decreased as the transit time increased. Nearly all fish caught were subjected to neither good handling nor low temperature despite the availability of good handling facilities. Nevertheles, the fish quality remained fairly good up to the point of soon after auctioning (pH’s<7 and organoleptic scores >7). When alone, none of the quality predictors affected the fish quality. However, when the fishing techniques were compounded the quality predictors significantly affected the fish quality. Regression analysis showed that, when the fishing techniques were uncompounded, 73.96% of the fish quality was determined by fishing with purse seine, cantrang, boatliftnet and fish transit time. When fishing techniques were compounded,however, the fishing techniques, on-board handling methods, on-board and on landing site handling facilities, and the fish transit time contributed 73.96% effect to the fish quality. The PCA analysis showed that as much as 52.52% and 27.27% the fish quality were determined by the purse seine and cantrang, respectively.